Impact of the degree of internationalization, innovation and knowledge management system on performance of Malaysian multinational companies - Anari, Hamideh Pouresmaeili (2016)
What drives successful internationalization and superior performance while firms are attempting to expand their business in global markets? As one of the most imperative questions in international business, many researchers have been trying to find the best answer for that, however, the existing literature shows inconsistency and ambiguity in findings. The present research investigates determinants of firms’ degree of internationalization (DoI) and performance, as well as examining the relationship between DoI and performance in the context of Malaysia. Specially, this study focuses on the mediating role of innovation on DoI-performance relationship, and moderating role of knowledge management system (KMS) toward innovation and performance relationship. Although, antecedents of DoI and performance, and relationship between these two factors have been widely studied in the literature, but these studies are mainly based on developed countries. Hence, lack of similar studies in Malaysia, as a fast growing economy with increasing rate of outward FDI, underpinning the aim of this study “to achieve a deeper understanding of Malaysian firms’ internationalization and performance”. This research develops five research questions and an integrated theoretical framework from multiple disciplines describing firms’ internationalization and performance implication grounded mainly on Uppsala theory and some other supportive approaches. A quantitative research method was implemented based on the empirical data collected by utilizing a self-administrated questionnaire from 226 Malaysian publicly listed firms having business in foreign markets. The partial least square (PLS) technique was adopted in data analysis process, because it works well when sample size is small, model is complex and formative constructs. In lights of findings from this study, high DoI and performance in Malaysian internationalizing firms are outcomes of firms’ strong networking capabilities, high entrepreneurial orientation, supportive home-government attitude, and higher entry mode diversity. Further, results show firms’ high DoI can be predicted with higher industry competition intensity, while impact of industry competition intensity on firm performance is not supported in the context of Malaysia. As predicted, there was a positive linear relationship between internationalizing firms’ DoI and performance in the context of Malaysia. In the process of firms’ internationalization, firms are exposed to different environment with higher competition and different culture, which creates higher learning opportunities, enables them to access different valuable information from various sources, allows them to acquire novel ideas, and hence leads to increase firm’s innovation and eventually firms’ performance. Therefore, based on the findings of this study it appears that innovation mediates relationship between DoI and performance and makes great contribution to the DoI-P literature. The moderating role of KMS towards innovation and performance relationship also was found to be significant, which it makes also considerable contribution to the body of knowledge by testing a new moderating variable toward innovation-performance relationship and also examining it in a new research setting, Malaysia. The unique and substantial contribution of this study to the existing literature was framing a conceptual model between DoI and performance, while integrating their antecedents into the framework, and most importantly, testing the mediating role of innovation. Majority of prior studies postulated direct and indirect DoI-performance relationship while ignoring the role of intervening variables, particularly mediating variables. Finally, this research found empirical confirmations to support the proposed new multidisciplinary theoretical framework, and advanced the management, entrepreneurship, strategic management, international business, and marketing literature. Research implications and recommendations were also provided.